Evaluation of air dielectric four-terminal-pair capacitance standards using resonance frequency of impedance elements. (March 2017) - Satish; Kumar, Sachin; Babita; John, Thomas; Saxena, A.K.
Graphical abstract: Highlights: A new method is proposed for characterization of 4TP capacitance standards. Frequency characteristics and associated uncertainty have been computed as per GUM. Capacitive and inductive components of electrical equivalent circuit are estimated. It will help in establishing the calibration services for capacitance standards. Abstract: A new method is proposed for the evaluation of air dielectric four-terminal-pair capacitance standards of nominal values 100 pF and 1000 pF using resonance frequency of impedance elements. It involves the determination of residual inductive and capacitive parameters of simple electrical-circuit-model of capacitance standards and thereafter computation of effective capacitance as a function of frequency up-to 10 MHz. The reference capacitance and residual capacitive parameters are measured using capacitance bridge and residual inductive parameters are estimated using measured resonance frequencies. The reported work will be helpful in the establishment of calibration services for capacitances up-to 10 MHz at CSIR-National Physical Laboratory. The uncertainty in measurement of effective capacitance is evaluated at k  = 2 as per guide to the expression of uncertainty in measurement. The uncertainty budgets for 100 pF and 1000 pF capacitance standards at 1 MHz and 10 MHz respectively are also provided to analyze the sources of uncertainty contributing to the final uncertainty in measurement.